Characterization of filamentous cyanobacteria and their effect on slow sand filters - Feijoo Rey,Iria (2024)
Safe and clean drinking water delivery is challenged by climate change, as elevated temperatures can promote the growth of pathogens and other detrimental microorganisms. The microbial processes underlying drinking water production in slow sand filters (SSFs) are largely uncharacterized, limiting the possibilities of improving this technology. Periodical clogging, potentially by microbes, disrupts the flow and necessitates the removal of the top sand layer. This study aimed to identify microbial causes of SSF clogging by relating the differential pressure of all SSFs in a drinking water treatment plant (n=20) to the abundance of specific taxa within the sand biofilm, estimated by 16s rRNA amplicon sequencing and qPCR. Phylum-level microbial signatures of clogged filters were determined using coda4microbiome and glmnet. The models explained 78% and 70% of the variation in head loss, respectively, and identified phylum Cyanobacteria as the most important factor increasing head loss. Cyanobacteria have been suggested as possible clogging causes in previous studies and may produce taste-and-odor compounds and cyanotoxins. To our knowledge, none have been isolated from SSFs, thus their impact on water quality and filter function is unknown. Cultivation of 3 filamentous cyanobacteria was achieved from SSFs, representing the first whole genome sequences of the poorly defined Anagnostidinema clade. Supplementation with vitamin B7 (biotin) lead to improved growth. The lack of B7 biosynthetic pathways in our isolates, suggests that cross-feeding occurs in the SSF ecosystem. Further analysis of pathways implicated in drinking water safety and slow sand filter operation is recommended. Understanding cyanobacterial growth conditions in SSFs is a step towards the definition of their ecological role in these communities. Eventually, community engineering directed toward Cyanobacteria may improve filtration efficacies and operational management of the treatment plants.